2006
DOI: 10.1017/s0307472200014565
|View full text |Cite
|
Sign up to set email alerts
|

Digital images and art historians – Compare and contrast revisited

Abstract: As the number of digital images available to art historians grows apace, it is perhaps an opportune moment to consider what impact digital images have had on the discipline and on the work methods of art historians. This paper revisits the findings of a research project – Compare and contrast – focusing on the attitudes of art historians towards digital image technologies, the role of the technologies in the different phases and activities of the research process, the tools and their potential, and barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Studies such as Chen (2001), Graham and Bailey (2006) and Matusiak (2006) discuss the issues related to the user's search skills. Graham and Bailey (2006) note that while some of their participants (art historians) complained about the lack of access to the technology, others did not have a general understanding of how to use the available technology and worried about the learning curve.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies such as Chen (2001), Graham and Bailey (2006) and Matusiak (2006) discuss the issues related to the user's search skills. Graham and Bailey (2006) note that while some of their participants (art historians) complained about the lack of access to the technology, others did not have a general understanding of how to use the available technology and worried about the learning curve.…”
Section: Resultsmentioning
confidence: 99%
“…Studies such as Chen (2001), Graham and Bailey (2006) and Matusiak (2006) discuss the issues related to the user's search skills. Graham and Bailey (2006) note that while some of their participants (art historians) complained about the lack of access to the technology, others did not have a general understanding of how to use the available technology and worried about the learning curve. In a different study, Matusiak (2006) found that participants who are less confident with their digital search skills tend to rely on browsing functionality provided for image search than on using keyword search.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, a standard pedagogical tool is the comparative analysis essay. In this exercise, students choose two pieces of art, often originating from differing eras or styles, and examine both the parallels and distinctions in their form, technique, and thematic content [5]. This activity prompts students to critically evaluate the influence of varying historical contexts and artistic movements on visual representation.…”
Section: Introductionmentioning
confidence: 99%